Involvement of DNA gyrase in replication and transcription of bacteriophage T7 DNA. - De Wyngaert, M (1979)
Growth of bacteriophage T7 is inhibited by the antibiotic coumermycin A1, an inhibitor of the Escherichia coli DNA gyrase. Since growth of the phage is insensitive to the antibiotic in strains containing a coumermycin-resistant DNA gyrase, this enzyme appears to be required for phage growth. We have investigated the effect of coumermycin on the kinetics of DNA, RNA, and protein synthesis during T7 infection. DNA synthesis is completely inhibited by the antibiotic. In addition, coumermycin significantly inhibits transcription of late but not early genes. Thus, E. coli DNA gyrase may play an important role in transcription as well as in replication of T7 DNA.